Electrical and optical properties of p-type CuFe1-xSn xO2 (x = 0.03, 0.05) delafossite-oxide - Ruttanapun, Chesta; Boonchom, Banjong; Thongkam, Montree; Kongtaweelert, Samart; Thanachayanont, Chanchana; Wichainchai, Aree (My University, 2013)
The CuFe1-xSnxO2 (x = 0.03, 0.05) delafossite samples have been synthesized by a solid-state reaction to investigate electrical and optical properties of the transparent conducting oxide materials. Crystal structure was characterized by XRD. The electrical conductivity and Seebeck coefficient were measured in the high temperature range of 300 to 960 K, while the Hall coefficient, XPS, and UV-VIS-NIR spectra were analyzed at room temperature. The XRD peaks of the samples indicate the delafossite structure phase, and the XPS spectra reveal the stable Sn 2+-doping state. The Seebeck and Hall coefficient display a positive sign indicating the p-type conducting oxide. The optical allowed direct gap is 3.45 eV as a visible-transparent material. The activation energies for polaron hopping between Sn2+ sites and Fe3+ sites of 36 and 32 meV are obtained from the samples having x = 0.03 and 0.05, respectively. The CuFe1-xSnxO2 delafossite oxide compounds, of which the Fe3+ sites in the CuFeO2 are substituted by the Sn2+ ions, are p-type transparent conducting oxide materials. The activation energy is found to decrease with an increased in Sn content. © 2013 American Institute of Physics.